A Molecular CO2 Reduction Catalyst Based on Giant Polyoxometalate Mo368 - Das, Santu; Balaraju, Tuniki; Barman, Soumitra; Sreejith, S. S.; Pochamoni, Ramudu; Roy, Soumyajit (Frontiers in Chemistry, 2018)
Photocatalytic CO2 reduction in water is one of the most attractive research pursuits of our time. In this article we report a giant polyoxometalate Mo368 based homogeneous catalytic system, which efficiently reduces CO2 to formic acid with a maximum turnover number (TON) of 27,666, turnover frequency (TOF) of 4,611 h−1 and external quantum efficiency of the reaction is 0.6%. The catalytic system oxidizes water and releases electrons, and these electrons are further utilized for the reduction of CO2 to formic acid. A maximum of 8.3 mmol of formic acid was observed with the loading of 0.3 μmol of the catalyst. Our catalyst material is also stable throughout the reaction. The starting materials for this experiment are CO2 and H2O and the end products are HCOOH and O2. The formic acid formed in this reaction is an important H2 gas carrier and thus significant in renewable energy research.